S-nitrosylation of the zinc finger protein SRG1 regulates plant immunity. Issue 1 (December 2018) - Cui, Beimi; Pan, Qiaona; Clarke, David; Villarreal, Marisol; Umbreen, Saima; Yuan, Bo; Shan, Weixing; Jiang, Jihong; Loake, Gary
Abstract Nitric oxide (NO) orchestrates a plethora of incongruent plant immune responses, including the reprograming of global gene expression. However, the cognate molecular mechanisms remain largely unknown. Here we show a zinc finger transcription factor (ZF-TF), SRG1, is a central target of NO bioactivity during plant immunity, where it functions as a positive regulator. NO accumulation promotesSRG1 expression and subsequently SRG1 occupies a repeated canonical sequence within target promoters. An EAR domain enables SRG1 to recruit the corepressor TOPLESS, suppressing target gene expression. Sustained NO synthesis drives SRG1S -nitrosylation predominantly at Cys87, relieving both SRG1 DNA binding and transcriptional repression activity. Accordingly, mutation of Cys87 compromises NO-mediated control of SRG1-dependent transcriptional suppression. Thus, the SRG1-SNO formation may contribute to a negative feedback loop that attenuates the plant immune response. SRG1 Cys87 is evolutionary conserved and thus may be a target for redox regulation of ZF-TF function across phylogenetic kingdoms. Upon pathogen infection plants accumulate nitric oxide which subsequently regulates defence gene expression. Here, the authors show thatS -nitrosylation of the zinc finger transcription factor SRG1 affects transcriptional suppression and contributes to activation of defence responses.